Clinical efficacy of probiotics in the treatment of alcoholic liver disease: a systematic review and meta-analysis - Xiong, Shi-Ying; Wu, Gui-Sheng; Li, Chun; Ma, Wenzhe; Luo, Huai-Rong (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: Alcoholic liver disease (ALD) is a liver damage disease caused by long-term heavy drinking. Currently, there is no targeted pharmaceutical intervention available for the treatment of this disease. To address this, this paper evaluates the efficacy and safety of probiotic preparation in treating ALD through conducting a meta-analysis, and provides a valuable insight for clinical decision-making. Methods: A systematic search was conducted across databases, including PubMed, Embase, Web of Science, Cochrane Library, CNKI, VIP, Wanfang, and CBM from the inception dates to October 15, 2023, to identify clinical randomized controlled trials on probiotic preparations in the treatment of ALD. After the literature underwent screening, data extraction, and quality assessment, RevMan 5.3 and Stata 14.2 were employed for data analysis and processing. Results: A total of 9 randomized controlled trials fulfilled the inclusion criteria. The results of the meta-analysis showed that probiotic preparation could significantly improve the liver function of patients with alcoholic liver disease compared with the control group. Probiotic intervention led to a significant reduction in the levels of alanine aminotransferase (MD=-13.36,95%CI:-15.58,-10.91;P<0.00001),aspartate aminotransferase (MD=-16.99,95%CI:-20.38,-13.59;P<0.00001),γ-glutamyl transpeptidase (MD=-18.79,95% CI:-28.23,-9.34; P<0.0001). Concurrently, the level of serum albumin (MD=0.19,95% CI:0.02,0.36;P=0.03) was increased. Furthermore, probiotic intervention could also modulate the composition of intestinal flora in patients with alcoholic liver disease, leading to an augmentation in Bifidobacteria and a reduction in Escherichia coli. However, in patients with alcoholic liver disease, probiotic intervention showed no significant effects on total bilirubin (MD=-0.01,95% CI:-0.17,0.15;P=0.91), tumor necrosis factor-α (MD=0.03,95% CI:-0.86,0.92;P=0.94) and interleukin-6 (MD=-5.3,95% CI:-16.04,5.45;P=0.33). Conclusion: The meta-analysis indicates that probiotics can improve liver function in alcoholic liver disease, reduce inflammatory responses, regulate intestinal flora, which have potential value in the treatment of alcoholic liver disease